2000
DOI: 10.1021/jp0028397
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of 7-Azaindole, Its Doubly-H-Bonded Base-Pair, and Corresponding Proton-Transfer-Tautomer Dimeric Species, via Defining Experimental and Theoretical Results

Abstract: Photophysical research on the experimental and theoretical bases for the biprotonic transfer in the doubly-H-bonded dimer of 7-azaindole (7AI) is reported. The spectroscopic properties of the 7AI monomer, the normal-tautomer dimer, and the proton-transfer tautomer dimer are delineated by absorption, fluorescence and excitation spectra. The monomeric 7AI molecule is shown to exist at 10-6 M in hydrocarbon solution at 298 K, and the pure dimer at temperatures below 227 K in 10-4 M solution in 2-methylbutane (2MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 49 publications
(99 reference statements)
6
93
0
1
Order By: Relevance
“…Calculations for the 7AI dimerization process, 7A I ϩ 7A I 3 (7A I) 2 , at the DFT(B3LYP)͞6-31G** level, indicate that the equilibrium is spontaneous in the gas phase, with ⌬G°2 98K ϭ Ϫ4.42 kcal͞mol, which is consistent with reported values in inert solvents. In fact, El-Bayoumi and co-workers (34) obtained a value of Ϫ4.5 kcal͞mol in 3-methylpentane, and Chou et al (35) measured Ϫ4.54 Ϯ 0.15 kcal͞mol in cyclohexane.…”
Section: Dimerization Modes Of 7ai In Adiabatic Nozzle Supercooled Mosupporting
confidence: 85%
“…Calculations for the 7AI dimerization process, 7A I ϩ 7A I 3 (7A I) 2 , at the DFT(B3LYP)͞6-31G** level, indicate that the equilibrium is spontaneous in the gas phase, with ⌬G°2 98K ϭ Ϫ4.42 kcal͞mol, which is consistent with reported values in inert solvents. In fact, El-Bayoumi and co-workers (34) obtained a value of Ϫ4.5 kcal͞mol in 3-methylpentane, and Chou et al (35) measured Ϫ4.54 Ϯ 0.15 kcal͞mol in cyclohexane.…”
Section: Dimerization Modes Of 7ai In Adiabatic Nozzle Supercooled Mosupporting
confidence: 85%
“…The method executed in a previous set of papers (2)(3)(4)(5)(6) and in the companion paper (1) allows us to propose an alternative mechanism for the double-proton transfer of the classic 7AI dimer (see below). The method used is based on the following theoretical levels of calculation.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The doubly hydrogen-bonded dimer of 7-azaindole is a prototypical system showing such a reaction in the photoexcited state. This dimer has served as one of the most central model systems, and hence its photochemistry and photophysics have been extensively studied for more than three decades (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Spectroscopic measurements revealed that the 7-azaindole dimer exhibits a double proton transfer reaction after photoexcitation ( Fig.…”
mentioning
confidence: 99%
“…The two different interpretations for femtosecond dynamics of the 7-azaindole dimer in solution triggered very intense debates, and the mechanism of the double proton transfer has been a central issue of the discussion (17,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Detailed theoretical calculations for the excited-state potential energy surface along the proton transfer coordinate have been performed to examine the existence of a local minimum corresponding to the intermediate species (24,30,(34)(35)(36).…”
mentioning
confidence: 99%